Exposure and Use of Mobile Media Devices by Young Children - Kabali, Hilda K; Irigoyen, Matilde M; Nunez-Davis, Rosemary; Budacki, Jennifer G; Mohanty, Sweta H; Leister, Kristin P; Bonner, Jr, Robert L (Pediatrics (Evanston), 2015)
Research on children's use of mobile media devices lags behind its adoption. The objective of this study was to examine young children's exposure to and use of mobile media devices. Cross-sectional study of 350 children aged 6 months to 4 years seen October to November 2014 at a pediatric clinic in an urban, low-income, minority community. The survey was adapted from Common Sense Media's 2013 nationwide survey. Most households had television (97%), tablets (83%), and smartphones (77%). At age 4, half the children had their own television and three-fourths their own mobile device. Almost all children (96.6%) used mobile devices, and most started using before age 1. Parents gave children devices when doing house chores (70%), to keep them calm (65%), and at bedtime (29%). At age 2, most children used a device daily and spent comparable screen time on television and mobile devices. Most 3- and 4-year-olds used devices without help, and one-third engaged in media multitasking. Content delivery applications such as YouTube and Netflix were popular. Child ownership of device, age at first use, and daily use were not associated with ethnicity or parent education. Young children in an urban, low-income, minority community had almost universal exposure to mobile devices, and most had their own device by age 4. The patterns of use suggest early adoption, frequent and independent use, and media multitasking. Studies are urgently needed to update recommendations for families and providers on the use of mobile media by young children.